(Not) “just your nature”. Diagnostic journeys of adults with neurofibromatosis type 1 in Poland - Kowal, Katarzyna; Domaradzki, Jan (Frontiers in Genetics, 2026)
BackgroundNeurofibromatosis type 1 (NF1) is a rare autosomal dominant disorder that presents complex physical, emotional, and social challenges. Despite clear diagnostic criteria, NF1 is often diagnosed late due to vague early symptoms, everyday or non-medical interpretations of early signs, and limited access to specialists and genetic testing. This study explores how individuals with NF1 experience the diagnostic process in this context.MethodsNinety-three adults with medically confirmed NF1 participated in in-depth interviews conducted between August 1 and 31 December 2020. Data were analyzed using reflexive thematic analysis, following Braun and Clarke’s six-phase framework to explore patterns in participants’ experiences and meaning-making related to diagnosis.ResultsThe diagnostic pathway for NF1 was often prolonged, fragmented, and emotionally taxing. Delays frequently stemmed from the normalization of early signs (e.g., café-au-lait macules or subcutaneous nodules) by both families and physicians. Many participants received their diagnosis incidentally, or only after persistent self-advocacy, parental initiative, or the diagnosis of their child. While some family members, particularly mothers, played an active diagnostic role, others responded with denial, minimization, or reluctance to discuss symptoms, which in turn prolonged the search for answers. Structural factors, such as limited NF1-specific familiarity among primary care providers, constrained referral pathways, and regional disparities, further complicated the diagnostic odyssey. The unpredictability and burden of diagnosis often led to frustration and emotional fatigue, particularly among those who lacked a family history of the disease.ConclusionThis study emphasizes the need for earlier NF1 recognition through enhanced clinician awareness, better diagnostic coordination, and access to genetic and psychosocial support. It also highlights the role of patient agency and the emotional cost of delayed diagnosis in rare diseases. These findings point to several actionable priorities, including the need to strengthen NF1-specific training for primary care physicians, implement clearer referral pathways, and expand access to genetic counselling and psychosocial support.